A Review on Development and Importance of Nanoemulsions - Sharma, Pawan; Mittal, Priyanka; Namdev, Abhisek; Agrawal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2015)
Nanoemulsions are novel drug delivery systems consisting of emulsified oil and water systems with mean droplet diameters ranging from 50 to 1000 nm. Usually, the average droplet size is between 100 and 500 nm and can exist as oil-in-water (o/w) or water-in-oil (w/o) form, where the core of the particle is either oil or water, respectively. Nanoemulsions are made from pharmaceutical surfactants that are generally regarded as safe (GRAS). The surfactant type and concentration in the aqueous phase are chosen to provide good stability against coalescence. The capacity of nanoemulsions to dissolve large quantities of low soluble drugs along with their mutual compatibility and ability to protect the drugs from hydrolysis and enzymatic degradation make them ideal drug delivery vectors. This review provides brief information about method of preparation and evaluation of nanoemulsion as drug carriers for improving the delivery of therapeutic agents [1].